Modeling anthropogenically controlled secondary organic aerosols in a megacity: a simplified framework for global and climate models - A. Hodzic (Geoscientific Model Development, 2011)
A simplified parameterization for secondary organic aerosol (SOA) formation in polluted air and biomass burning smoke is tested and optimized in this work, towards the goal of a computationally inexpensive method to calculate pollution and biomass burning SOA mass and hygroscopicity in global and climate models. A regional chemistry-transport model is used as the testbed for the parameterization, which is compared against observations from the Mexico City metropolitan area during the MILAGRO 2006 field experiment. The empirical parameterization is based on the observed proportionality of SOA concentrations to excess CO and photochemical age of the airmass. The approach consists in emitting an organic gas as lumped SOA precursor surrogate proportional to anthropogenic or biomass burning CO emissions according to the observed ratio between SOA and CO in aged air, and reacting this surrogate with OH into a single non-volatile species that condenses to form SOA. An emission factor of 0.08 g of the lumped SOA precursor per g of CO and a rate constant with OH of 1.25 × 10−11 cm3 molecule−1 s−1 reproduce the observed average SOA mass within 30 % in the urban area and downwind. When a 2.5 times slower rate is used (5 × 10−12 cm3 molecule−1 s−1) the predicted SOA amount and temporal evolution is nearly identical to the results obtained with SOA formation from semi-volatile and intermediate volatility primary organic vapors according to the Robinson et al. (2007) formulation. Our simplified method has the advantage of being much less computationally expensive than Robinson-type methods, and can be used in regions where the emissions of SOA precursors are not yet available. As the aged SOA/ΔCO ratios are rather consistent globally for anthropogenic pollution, this parameterization could be reasonably tested in and applied to other regions. The evolution of oxygen-to-carbon ratio was also empirically modeled and the predicted levels were found to be in reasonable agreement with observations. The potential enhancement of biogenic SOA by anthropogenic pollution, which has been suggested to play a major role in global SOA formation, is also tested using two simple parameterizations. Our results suggest that the pollution enhancement of biogenic SOA could provide additional SOA, but does not however explain the concentrations or the spatial and temporal variations of measured SOA mass in the vicinity of Mexico City, which appears to be controlled by anthropogenic sources. The contribution of the biomass burning to the predicted SOA is less than 10% during the studied period.